Clinical features and diagnostic criteria of diseases of esophagogastroduodenal zone in patients with gallstone disease after cholecystectomy - I. V. Kozlova; Ye. V. Graushkina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To reveal frequency of clinical and structural and functional features of esophagogastroduodenal diseases at patients with gallstone disease (GSD) in various terms after cholecystectomy.Material and methods. Questioning of 625 person with cholecystectomy in past history was carried out, 94 patients with GSD, that underwent cholecystectomy, and 62 not operated patients with GSD were prospectively investigated. All patients were examined by endoscopic and histological studies, biochemical and immunoenzyme tests with assessment of the level of elastase, glycosaminoglycans, protein-bound hydroxy-proline, interleukins 1, 8, 10 in blood serum, in part of patients 24-hour pH-metry was done. Results. In operated patients, with increase of time, past after surgery, significantly more frequent atrophic and reflux-gastritis, duodenogastric reflux, duodenitis were found, atrophy, metaplasia and dysplasia of stomach epithelium grow. Inflammatory and erosive-ulcerative changes of esophagogastroduodenal mucosa in these patients develop and progress on a background of disbalance of cytokines and metabolites of connective tissue in blood serum, the most severe in terms over 3 years after cholecystectomy. After operation secretory and motor dysfunction of gastroduodenal zone aggravated: significantly more frequent decrease secretion of muriatic acid, duodenogastric and duodenogastroesophageal refluxes were found. Studying of the contents of interleukins, as well as parameters of reparation and destruction of connective tissue in blood serum have highly diagnostic value in evaluation of severity of changes of gastroduodenal zone. Patients with GSD after cholecystectomy, should be included to group of dispensary observation and the directional therapeutic management.Conclusions. Parameters of concentration of interleukins 1, 8, 10, elastase, glycosaminoglycans, proteinbound hydroxy-proline in blood serum can be used as additional criteria of noninvasive diagnostics of gastroduodenal diseases in postcholecystectomy patients.